Classic tales: Alice in Wonderland - STILTON, GERINIMO; GERINIMO STILTON (New York Scholastic, Inc, 2010)
a classic work of literary nonsense following a young girl named Alice who falls down a rabbit hole into a fantastical, illogical world.
Keywords: The story originated from a real-life; the importance of curiosity, and the absurdity of adult conventions